Analysis of Cryogenic Ammonia System for Energy Conservation - B. Raei; F. Shahraki; M. Khorrami; A. Ghadi (Iranica Journal of Energy and Environment, 2010)
There are several alternatives to enhance the efficiency of energy usage and to decrease energy losses. Pinch technology is the best method of approach to enhance energy efficiency. Heat exchangers network (HEN) of refrigeration unit of ammonia production process was analyzed to use pinch technology to decrease energy usage. The obtained results showed that pinch technology was unsuccessful for the shaft work targeting capabilities. In contrast, it is posed that for optimization of such systems, one should use the combined pinch and exergy analysis (CPEA) method. In this analysis CPEA method was used in the system. It was observed that the refrigeration system use cold streams for cooling the hot streams. Therefore, retrofitting the refrigeration cycle without changing the main process is impossible. Some suggestions were made for improving the refrigeration system, such as the use of economizer after cooler, multistage cycle and removal of the 111-FFD3 stream. It was also observed that the exchanger 128-E act as an intercooler and the flashed 110-F, 111-F and 112-F act as an economizer. In addition, ammonia refrigerant was used at three different temperatures of -33,-7 and 13.5 ˚C. Also, eliminated the 111-FFD3 stream bring about 2% reduction in exergy loss.